The Influence of Project-Based Brain-Writing Learning Model to Increase the Writing Skill toward Indonesian Subject at Primary School - Dayu, Dian Permatasari Kusuma; Haryanto, Haryanto (Universitas Negeri Semarang, 2020)
This study explained about the concept of project-based brain-writing learning model in the teaching and learning process of writing skill in Indonesian subject. Learning became the process to deliver the theory to the students through stimuli and responses. One of the aspects that were very important to determine the learning achievement was the using of learning strategy and the interactive learning media that could motivate the students in the learning process. The research has purposed to find the effect of the Brainwriting learning model based on project-based learning to improve Indonesian writing skills. The research method used an experimental method research design. The research population was five classes of Public Elementary School 1 Klegen Madiun. Analyzing the results that there is a significant effect of project-based learning brainwriting models on Indonesian writing skills. This study used a project-based brain-writing learning model that hopefully could give the easier learning process for the students.